PROACTIVE COPING DITINJAU DARI SELF EFFICACY PADA MAHASISWA YANG SEDANG MENYUSUN SKRIPSI DI PROGRAM STUDI SISTEM INFORMASI FAKULTAS TEKNOLOGI DAN ILMU KOMPUTER UNIVERSITAS PRIMA INDONESIA MEDAN - Sri Hartini, Sri Hartini (Mitra prima, 2023)
ABSTRACT This study aims to find out relationship between self efficacy and proactive coping on students are writing essay in study program information systems faculty of technology computer science in University of Prima Indonesia Medan. The hypothesis of this study states that there is a positive correlation between self efficacy and proactive coping, assuming that the higher self efficacy, the higher will proactive coping be and conversely the lower the self efficacy the lower will proactive coping be. The subjects of this study were 101 students at Faculty of Technology and Computer Science University of Prima Indonesia selected by purposive sampling method. Data were obtained from a scale to measure self efficacy and proactive coping. The calculation was performed by means of testing requirements analysis (assumption), which consists of normality test for distribution and linearity test for relationships. The data analysis used is Product Moment Correlation with SPSS 17 for Windows. The results of data analysis showed that the correlation coefficient was 0.506 with p 0.000 (p <0.05). It shows that there is a positive relationship between self efficacy and proactive coping. These results indicate that the contribution of a given variable of self efficacy to proactive coping is at 26 percent, while the remaining 74 percent is influenced by other factors not examined. From these results, it is concluded that the hypothesis stating that there is a positive correlation between self efficacy and proactive coping is acceptable. Keywords: Self Efficacy, Proactive Coping